Repellency and Feeding Deterrence Activity of Ageratum Conyzoides Against the Stored Grain Pests Tribolium Castaneum and Sitophilus Oryzae. Active Plant Parts and Composition - Alonso Amelot, Miguel Enrique; Avendaño, Marisabel; Aubert, Lianne; Avila, Jorge Luis (Ciencia)
The anti-insect materials, expressed as contact repellents, feeding inhibitors and modificators of the eficiency of conversion of ingested material (ECI), contained in the forb Ageratum conyzoides L. (Magnolionidae, Asteraceae) against the grain pests rice weevil Sitophilus oryzae and red flour beetle Tribolium castaneum¸ were studied by exhaustive extraction in hexane, dichloromethane, ethyl acetate, methanol and water of separate plant parts and the essential oil of fresh leaves. The primary activity in all orders was found in the low polarity extracts, and chiefly concentrated in the material stemming from the leaves. Bioassay-guided chromatographic isolation of the feeding deterrents yielded the known chromene precocene II as the sole active component. Antifeedant activity of this compound was quantitized as DE50 = 1.36 µg/mg in S. oryzae and 1.11 µg/mg for T. castaneum. The ecological status of A. conyzoides as a plant with semiochemical defenses is discussed